RESPONSES OF JATROPHA CURCAS SUPERIOR CLONES AGAINST DROUGHT STRESS - Machfud M.; Santoso I.; Slamet; Purwati R.D.; Herwati A.; Djumali (Russian Journal of Agricultural and Socio-Economic Sciences, 2023)
Superior clones of Jatropha curcas that will be released as superior varieties must be tested for drought stress tolerance. This study aims to examine the drought stress tolerance of superior clones of Jatropha. The study took place in the Green House of the Indonesian Sweetener and Fiber Crops Research Institute in Malang, East Java, Indonesia, from January to December 2021. The treatments were arranged in a split-plot design with 3 replications. The main plot consisted of 4 soil moisture levels (40, 60, 80, and 100% of field capacity), and the subplots consisted of 4 superior clones (HS-49xSP-65/32, IP-3AxSP-89/4, IP-3AxSP-65/11, IP-3PxSP-7/5) and a control clone (Jet-1 Agribun). The results showed that the clones tested were classified as susceptible – tolerant to water stress. Clones HS-49xSP-65/32 are classified as tolerant, clones IP-3AxSP-65/11 and IP-3PxSP-7/5 are classified as moderate, and clones IP-3AxSP-89/4 and Jet-1 Agribun are classified as susceptible.